Pengelolaan Keuangan Keluarga dalam Islam Agar Terhindar Dari Pinjaman Online - Shevchenkie, Irgie Ramdhan; Maulana, Deni (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Online loans have started to spread in society through advertisements on gadgets when opening applications, watching videos from YouTube, shopping centers and sometimes even daring to offer them to homes. Not a few families are trapped because they are offered low interest with an easy and fast disbursement process. In the end, due to minimal literacy about the dangers of online loans, many customers' personal data is misused by borrowers because they are unable to pay. Good financial management is one solution for individuals and families to avoid economic conflict. Especially for people who already have families, this is very important for the welfare of life in the future. Someone may borrow money not because it is difficult to find money, but rather to buy unnecessary items to follow desires rather than needs without financial planning. This study aims to avoid - especially Muslim families, from online loans with family financial management from Islamic religious reference sources. By taking wisdom from informal interviews which are also equipped with references from books and journals to discuss in more detail the dangers of online loans and the importance of family financial management from Islamic religious sources in maintaining the integrity of the household.